The key factors of evaluating agile approaches: a systematic literature review - Alaidaros, Hamzah; Omar, Mazni; Romli, Rohaida (ExcelingTech Publishers, 2019)
Currently, the housing sector is one of the Malaysian government’s main concerns as it is continuously facing various problems. This sector is endlessly struggling with enormous difficulties that have caused negative implications to the industry’s performance. Since a well governed corporate governance is said to be associated with better company performance, a number of corporate governance mechanisms are being employed in this study so as to test on their impact on the firms’ performance. Independence of board of directors (BOD) and audit committee (AC) members, non-duality and frequency of board meetings held per annum are among the CG mechanisms tested in relation to the firms’ performance, Tobin’s Q. The three-year period (2013-2015) data is taken from the annual reports and Thomson Reuters Data stream for all the companies in the property industry in Bursa Malaysia. Number of board meetings, CEO/Chairman non-duality, Independence of BOD members. These empirical evidences from this study would enhance the importance of incorporating corporate governance mechanisms and international diversification in relation to organizational performance for property industry.